(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Mahatma Gandhi and R.K. Narayan, notable figures in Indian history and literature respectively, advocated for educational systems focused on holistic development and moral integrity. Gandhi emphasized "Nai Talim," a principle promoting self-reliance and vocational training alongside academic studies. Narayan, through his fictional works, subtly critiqued the rote educational methods of his time, championing learning that nurtures creativity and character. In contemporary society, their ideals resonate in the growing emphasis on value-based education, critical thinking, and innovation, challenging traditional curriculum-centered approaches